(3HMGQ GdYdhes - (3eLghds ((3eMeO MSfs)
(3ChdgG (B:s
(3GdMeO ddg GdPj CfRd Ydi YHOg GdcJGH (B... (3aCbhd bO ecQJ aj faSj hGfWhJ (B.. (3LOj QShd Gddg Udi Gddg Ydjg hHGQc hSde hEdi eG GNJda GdfGS ajg aj CYGdg hCbhGdg hCMhGdg (B...s
(3BNQgG (B:s
.. (3hEPG bdfG dce gPG hHdZfGce gPG GdNHQ GdUGOb aSbWJ Yf PeJfG hfMf eHTQhf hefPQhf dce heaQbhf Hf GdMb hGdHGWd (B...(3bO Je cJGH HMGQ GdYdhe(B.s
(3JHUQI GdeDda (B:s
(3Tcc Bb HQRc WgQGfj aj fSHI GdcJGH dLYaQ GdUGObs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B3/45s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJhMjO hGdedd hGdfMds